Eksplorasi Bahan Aktif Rumput Laut Coklat (Phaeophyceae) sebagai Biolarvasida Aedes aegypti [Exploration of Brown Seaweed (Phaeophyceae) Active Subtance as Aedes aegypti Biolarvicides] - Moch. Amin Alamsjah; Ike Nur Firdhayani; Sri Subekti (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Exploration of seaweed on pharmacy has been developed. The recent studies found its capacity as biolarvacidal. The expert cited Manilal explained that seaweed secondary metabolites has a complex chemical structures with a different bioactivity capabilities. It also has varied capabilities, for pharmacy field, ecologic and as a toxic source. This study aim are to determined the capabilities of brown seaweed extracts P. gymnospora, S. filipendula, S. duplicatum, and S. polycystum as an Ae. aegypti larvicides and optimum dose for 50% mortality (LC50 ) of Ae. aegypti larvae. The research methods is experimental with 50% Ae. aegypti larvae mortality (LC50 ) or probit analyzis. The treatment research are P.gymnospora as E1, S. filipendula as E2, S. duplicatum E3, and S. polycystum as E4. The concentration of each 20 ppm (D1), 40 ppm (D2) , 60 ppm (D3), 80 ppm (D4) and 100 ppm (D5). Repetitions of each treatment three times. The results showed that extracting of P. gymnospora, S. filipendula, S. duplicatum, and S. polycystum have capability as Ae. aegypti larvicide. The optimum dose of the extract with the number of deaths is 50 % or LC50 P. gymnospora (40.19 ppm ± 0.21), S. duplicatum, S. Fillipendula, S. Polycystum more than 100 ppm. The discussion about active substance of brown seaweed, saponins, terpenoids, flavonoids and polivenol showed positive result and its dominance founded in P. gymnospora extract that is the best efficiency of LC50